2007
DOI: 10.3132/pcrj.2007.00039
|View full text |Cite
|
Sign up to set email alerts
|

Asthma: 1987-2007. What have we achieved and what are the persisting challenges?

Abstract: SummaryDespite an increasing prevalence of asthma, enormous advances have been made in our understanding and management of asthma over the last 20 years. Work begun two or three decades ago demonstrated the inflammatory nature of asthma, emphasised the need for regular treatment, and introduced the goal of maintaining normal lung function. More recent work demonstrated the benefits of adding a long-acting inhaled beta-agonist to low-dose inhaled steroids as an alternative to escalating the steroid dosage. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Our study revealed a change over time in the impact of BMI on lung function, and, furthermore, may suggest that, in subjects with self-reported asthma, there is an interaction between BMI and asthma status not found in subjects not reporting symptoms of asthma. Apart from suboptimal asthma control due to compliance-related issues [21,22], it is, therefore, likely that the observed increase in severity of asthma, as judged by FEV1, may be due to an increasing trend towards being overweight and obese, not least among subjects with self-reported asthma. The present study, however, did not reveal major clues towards understanding the mechanisms underlying the changes over time in prevalence of self-reported asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed a change over time in the impact of BMI on lung function, and, furthermore, may suggest that, in subjects with self-reported asthma, there is an interaction between BMI and asthma status not found in subjects not reporting symptoms of asthma. Apart from suboptimal asthma control due to compliance-related issues [21,22], it is, therefore, likely that the observed increase in severity of asthma, as judged by FEV1, may be due to an increasing trend towards being overweight and obese, not least among subjects with self-reported asthma. The present study, however, did not reveal major clues towards understanding the mechanisms underlying the changes over time in prevalence of self-reported asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published National Health and Wellness Study 4 suggests that these older studies of asthma control may not reflect the present control outputs. In this study of 37 000 randomly chosen individuals (all adults), in response to the question 'Have you ever been diagnosed as having asthma by a physician?'…”
Section: How Well Have We Been Doing With Asthma Control?mentioning
confidence: 99%
“…Martin Partridge found that 55% of doctors thought that their patients were well controlled, despite poor control of such patients being revealed in the Asthma Control Questionnaire. 4 The now famous Suissa Study 7 which demonstrated that use of inhaled corticosteroids (ICSs) regularly resulted in falling asthma mortality, upholds the principle that non-adherence significantly increases the risk of death from asthma. All of these methods have been discussed in detail in other reviews.…”
Section: Underestimating Asthma (Doctor and Patient)mentioning
confidence: 99%
“…These include the need for more aggressive implementation of self-management education for patients and the need for the physician to discuss and alleviate patient concerns regarding medication safety (27,28). Partridge (29) and Roberts et al (30) highlighted the need for accurate diagnosis of patients with severe asthma and the development of a structured protocol-based approach to offset potential differences in treatment strategy between specialists with a particular interest in severe asthma and other respiratory physicians. In addition, the failure of patients to correctly use their prescribed medication is a significant challenge in asthma management (7,9).…”
Section: The Role Of Ics and Laba In Improving Asthma Controlmentioning
confidence: 99%